Palatal Dimensions and Its Correlation with the Circumference of Upper Anterior Teeth - Zeina M Ahmad (Al-Rafidain Dental Journal, 2009)
Aims: To put a bases for the prediction of the circumference of artificial anterior teeth depending on thepalatal dimensions Materials and methods: The study sample consists of 30 female and 32 male withclass I occlusion aged 19– 24 years .The dimensions of the palatal vault and the circumferences of upperanterior teeth were recorded with digital venire caliper and analyzed with SPSS program (version 11). Results:significant correlation was found between the dimension of the palatal vault and the circumference ofupper anterior teeth. Conclusions: the angle of circumferences of upper anterior teeth of narrow short anddeep palate will be more tapered than those one in the wide, long and shallow palate.